Stock repurchase announcement effect stock price / Ahmad Tarmizi Abd Shukor - Abd Shukor, Ahmad Tarmizi (2007)
This research paper studied the effect of stock price repurchase announcement on stock price for company who do stock repurchase program. The daily data collected from October 2006 to January 2007. The objective of this study are to examine the effect of stock repurchase announcement to stock price in bursa Malaysia three days before announcement day, on the announcement day and three days after announcement days. The method using are descriptive, regression and correlation model. These results imply that firms are not punished for failing to carry through on repurchase announcement, and that investor only focus on the repurchase announcement.